A note on poverty, inequality and growth - George Korres; Emmanuel Marmaras; George Tsobanoglou (European Regional Science Association (ERSA), 2004)
How inequality is generated and how it reproduces over time? This has been a major concern of social scientists for more than a century. The changes in aggregate or average income is a good measure for economic growth but is far from being the only one. There is an increasing “inequality” throughout the world. Over the period 1960-2000, the richest 5 % of the world's nations averaged a per-capita income that was about twenty-nine times the corresponding figure for the poorest 5 %. Poverty also affects other forms of economic and social functioning. The measurement of poverty is based on the notion of poverty line, which is constructed from monetary estimates of minimum needs. Poverty is highly correlated with the lack of education, and there is an intimate connection between nutrition and poverty. The measurement of inequality is a highly controversial one. It is a field in which there are large differences in social judgments, which translate themselves into differences in social judgments, such as the measure of inequality or the choice of equivalence scale. Social and Economic indicators demonstrate the data for the population based measures on economic, social and health outcomes and answer the question about inequality and well being. This article attempts to examine the relationship between inequality and the process of socio-economic development and also to overview the theories of income inequality and to measure the income distribution and moreover to investigate the role and the effects on socio-economic growth. Keywords: Income distribution, inequality, poverty, convergence, growth.
Keywords: 330; Income distribution; inequality; poverty; convergence; growth